Right-wing populism in the European Union and the rise of Germany's Alternative für Deutschland (AfD) and Hungary's Jobbik - Bleher, Saskia (Department of Political Studies, 2020)
The purpose of this thesis is it to investigate the socio-political conditions that gave rise to right-wing populism (RWP) in Germany and Hungary. It ascertains reasons for increasing right-wing populist attitudes in these two countries by tracing the emergence of the German Alternative für Deutschland (AfD) and the Hungarian Movement for a better Hungary (Jobbik). The choice to compare these parties was influenced by considerations relating to their roles as main opposition parties in their respective countries’ parliaments as well as the fact that they were catapulted to political prominence as right-wing populist parties in the aftermath of the refugee crisis of 2015. Examining the causes for the increase of RWP across Europe is indispensable for purposes of understanding the everchanging political landscape of the European Union (EU) and the continued threat RWP poses to liberal democratic values in that region. Furthermore, it is necessary to comprehend the undercurrents besetting the two societies’ social fabrics and political nomenclatures as well as their roles in precipitating rightwing populist movements that have gone on dominate their respective polities. To unearth the circumstances behind the rise of RWP as a political phenomenon, the Most Different Systems Design will be utilized to identify factors which account for the success of the AfD and Jobbik in their respective countries. To carry out this task both the Cultural Backlash Thesis (CBT) and the Economic Insecurity Perspective (EIP) are employed as theoretical nodal points to ascertain each of the two countries’ unique set of socio-political and socioeconomic circumstances that propelled right-wing parties to political prominence. This thesis argues that both the CBT and EIP have been at the centre of why right-wing populism has been on the rise in the EU in recent times. Accounting for the exponential rise of Jobbik and the AfD is the exploitation of growing nationalist sentiments by both parties fuelled by fear of the loss of traditional norms and values since the refugee crisis. By focusing on traditional values and their countries’ cultural identities, the two right-wing populist parties inadvertently exclude minority groups on a continued basis. Furthermore, this study claims that while cultural discontents account for the rise of both parties, economic grievances are only applicable in Jobbik’s case alone. This is due to the fact that Germany suffers from less economic difficulties as EU’s strongest economy, whereas Hungary’s own has been performing below par, which has been aggravated by high levels of corruption in the public sector. Hence, Jobbik’s rise has been aided by economic and cultural frustrations as a result of the so-called foreign infiltration whereas the AfD’s is attributed to growing cultural and nationalist grievances gaining a foothold in Germany.